2018
DOI: 10.17219/acem/90766
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the effect on lower extremity fracture healing of collagen-based fusion material containing 2 different calcium phosphate salts: An experimental rat model

Abstract: Background. Collagen-based synthetic bone grafts which contain tricalcium phosphate (TCP) and hydroxyapatite (HA), and collagen-based synthetic bone grafts containing only TCP have some advantages compared to autografts. Therefore, these grafts are frequently used to fill bone defects and pseudoarthrosis. Objectives. The aim of this study was to evaluate and compare the clinical, radiological and histopathological effects of TCP-HA and TCP alone + Type-1 collagen in healing lower extremity fractures in a pseud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…et al indicated, it is extremely difficult to connect nanoparticles with natural polymers to obtain a homogenous composite [ 6 ]. Nevertheless, according to Aksekili A.M.E. et al [ 7 ], scaffolds with different types of composition with hydroxyapatite (HA) appear promising for the treatment of pseudoarthrosis, due to their biocompatibility and long biodegradation time. Furthermore, in the review by Miriam Filippi et al [ 8 ], we find many examples of different materials based on natural polymers and hydroxyapatite, such as hyaluronic acid, keratin, fibrin, gelatin, silk fibroin (SF), collagen, heparin, chitosan (CTS), alginate, starch, agar, dextran, cellulose, carrageenans or gellan gum.…”
Section: Introductionmentioning
confidence: 99%
“…et al indicated, it is extremely difficult to connect nanoparticles with natural polymers to obtain a homogenous composite [ 6 ]. Nevertheless, according to Aksekili A.M.E. et al [ 7 ], scaffolds with different types of composition with hydroxyapatite (HA) appear promising for the treatment of pseudoarthrosis, due to their biocompatibility and long biodegradation time. Furthermore, in the review by Miriam Filippi et al [ 8 ], we find many examples of different materials based on natural polymers and hydroxyapatite, such as hyaluronic acid, keratin, fibrin, gelatin, silk fibroin (SF), collagen, heparin, chitosan (CTS), alginate, starch, agar, dextran, cellulose, carrageenans or gellan gum.…”
Section: Introductionmentioning
confidence: 99%